МЕТОДИКА ИНСТРУМЕНТАЛЬНО МУЛЬТИЭЛЕМЕНТНОГО НЕЙТРОННО-АКТИВАЦИОННОГО АНАЛИЗА ПРИРОДНЫХ ОБЪЕКТОВ ЮЖНОГО ПРИАРАЛЬЯ - Жумамуратов, М.А. (SCIENCE and SOCIETY, 2019)
On the bases of experimental investigation of γ-irradiation spectra of probes activated with integral neutrons’ flow at different time factors the selectivity coefficient is calculated for every probe and elements. New data are obtained on mean content of more than 30 chemical elements in the content of natural water, soil, bottom sediment, aerosol dust and atmospheric precipitation.
Keywords: Karakalpakstan; water; neutron-activation analysis; chemical composition; intensity; subsoil waters; coefficient; river waters; collector waters